Religiosity and Pesantren Environment in Shaping Philanthropic Giving Behavior: An Empirical Study of Female Student Teachers at LAZISWAF Gontor - Muhammad Abdul Aziz; Shella Annisa Kurnia Pratiwi; Nurizal Ismail (AL-IKTISAB: Journal of Islamic Economic Law, 2026)
Islamic philanthropy, particularly ṣadaqah (voluntary charity), plays a crucial role in promoting social welfare and economic redistribution. However, the determinants of philanthropic behavior among individuals with limited financial capacity, such as students, remain underexplored in the literature. This study aims to examine the influence of religiosity and the pesantren environment on philanthropic giving behavior among female student teachers at LAZISWAF Gontor Putri 1. A unique phenomenon is observed at this location, where female student teachers demonstrate active participation in ṣadaqah despite lacking a stable fixed income.This research employs a quantitative approach with an explanatory design. Data were collected through structured questionnaires from 201 respondents selected using a simple random sampling technique. Data analysis was performed using multiple linear regression techniques via SPSS software to evaluate the relationships between variables.The results show that religiosity has a positive and significant effect on ṣadaqah behavior (β = 0.383, p < 0.05). Similarly, the pesantren environment has a significant positive influence (β = 0.369, p < 0.05), even demonstrating a slightly stronger statistical impact in reinforcing individual motivation through subjective norms. Simultaneously, this model accounts for 52.3% of the variance in philanthropic behavior (R² = 0.523).These findings indicate that internal religious commitment and a supportive socio-religious environment jointly shape sustainable philanthropic practices. This proves that value internalization and environmental reinforcement can effectively substitute for economic capacity in driving the act of sharing. This study contributes theoretically by introducing a value-based behavioral model rooted in pesantren culture. Practically, philanthropic institutions are encouraged to strengthen religious education and create supportive ecosystems to increase the participation of young donors in the future.